Beyond metabolic messengers: Bile acids and TGR5 as pharmacotherapeutic intervention for psychiatric disorders - Arief Gunawan Darmanto; Ting-Lin Yen; Jing-Shiun Jan; Tran Thanh Duy Linh; Rajeev Taliyan; Chih-Hao Yang; Joen-Rong Sheu (Pharmacological Research)
Psychiatric disorders pose a significant global health challenge, exacerbated by the COVID-19 pandemic and insufficiently addressed by the current treatments. This review explores the emerging role of bile acids and the TGR5 receptor in the pathophysiology of psychiatric conditions, emphasizing their signaling within the gut-brain axis. We detail the synthesis and systemic functions of bile acids, their transformation by gut microbiota, and their impact across various neuropsychiatric disorders, including major depressive disorder, general anxiety disorder, schizophrenia, autism spectrum disorder, and bipolar disorder. The review highlights how dysbiosis and altered bile acid metabolism contribute to the development and exacerbation of these neuropsychiatric disorders through mechanisms involving inflammation, oxidative stress, and neurotransmitter dysregulation. Importantly, we detail both pharmacological and non-pharmacological interventions that modulate TGR5 signaling, offering potential breakthroughs in treatment strategies. These include dietary adjustments to enhance beneficial bile acids production and the use of specific TGR5 agonists that have shown promise in preclinical and clinical settings for their regulatory effects on critical pathways such as cAMP-PKA, NRF2-mediated antioxidant responses, and neuroinflammation. By integrating findings from the dynamics of gut microbiota, bile acids metabolism, and TGR5 receptor related signaling events, this review underscores cutting-edge therapeutic approaches poised to revolutionize the management and treatment of psychiatric disorders.